أثر استخدام استراتيجية التدريس التبادلي في تنمية فهم المقروء لدى طالبات من قسم الإعداد اللغوي بجامعة الراية - Nur Hanifah (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Bahasa Arab Ar Raayah, 2018)
Learning strategies are the steps that the students use to enhance their learning process. Strategies are important in learning a language in particular, as they are effective, self- directed is able to offer progress in a smart way and can increase their self- confidence. In order to achieve the objectives of the study, the researcher was used a scientific method, that is the experimental method. Sample of the study consisted of thirty (30) female students from STIBA of Ar-Raayah, where the sample was divided into two groups: the experimental group consisted of (15) female students, and the control groups consisted of (15) female students. The instrument of the study is a test of reading skill before and after applying Reciprocal teaching, which paved the researchered to know the impact of using reciprocal teaching method in development of reading comprehension skill. This study had shown that there were good effect of using reciprocal teaching strategy in the development reading comprehension skill for students, proved that this strategy helps to develop of reading comprehension skill and measurement for variation method teaching in STIBA of Ar-Raayah.